O-176 Secondary ovarian insufficiency (SOI) - a new infertility diagnosis. (6th August 2021) - Gleicher, N; Darmon, S K; Albertini, D F; Barad, D H
Abstract: Study question: Can, in contrast to primary ovarian insufficiency (POI), ovarian insufficiency also be caused as a secondary event (SOI)? Summary answer: Adrenal hypo-androgenism, caused by insufficiency in androgen production by the zona reticularis, may mimic POI in clinical presentation. What is known already: A variety of small and large animal models have, especially at small growing follicle stages, conclusively demonstrated the dependence of normal follicle maturation on adequate testosterone levels, a process mediated via the androgen receptor on granulosa cells. Increasing clinical evidence, moreover, has demonstrated clinical improvements in oocyte numbers and oocyte quality following androgen supplementation at these stages in hypo-androgenic women with premature ovarian aging (POA). Whether adrenal hypo-androgenism in extreme cases can, however, also lead to complete ovarian insufficiency mimicking POI, is unknown. Study design, size, duration: Based on FSH levels >40.0 mIU/mL and amenorrhea, we searched our center's electronic research data bank for patients who between 2016-2018 presented with a diagnosis of presumed POI. Participants/materials, setting, methods: Among 78 POIs, 13 demonstrated low DHEAS (< 100 ug/dL), i.e., adrenal hypo-androgenism, 6 rejected egg donation and received DHEA (Fertinatal®, 25mg TID, Fertility Nutraceuticals, LLC, New York, N.Y., USA) and Coq10 (Ovoenergen®, 333mg TID, same manufacturer) before stimulation with 450IU FSH and 150 IU hMG (different manufacturers). All women were < age 41, demonstrated menopausal FSH (>40.0 mIU/mL), undetectable AMH, amenorrhea, > prior cycle cancellation, elevated SHBG, low total testosterone and low DHEAS (high DHEA/DHEAS). Main results and the role of chance: Out of the 6 patients so stimulated, 5 demonstrated follicular responses following DHEA supplementation and 2/6 conceived spontaneously and delivered healthy offspring. One of these two is currently in treatment for another child. Limitations, reasons for caution: To better understand adrenal control of ovaries via androgen production, further elucidation of endocrine signaling between adrenals and ovaries is required, including detection of unknown, though increasingly likely, feedback loops, considering that adrenals and ovaries share a primordium. Wider implications of the findings: We confirmed existence of SOI due to adrenal hypoandrogenism, defined its phenotype, demonstrating that some patients with alleged POI actually exhibit SOI. Better pregnancy chances with adrenal SOI than POI, reemphasize the importance of correct differential diagnoses to avoid premature referrals of women into third-party egg donations Trial registration number: N/A